Hours of Work, Labor Productivity, and Environmental Conditions: A Case Study - Crocker, Thomas D.; Horst, Robert L. (The Review of Economics and Statistics, 1981)
Livelihood measures of foregone and compensating earnings are frequently used as measures of economic losses due to realized or potential damages to the health of labor in-puts. Both measures as they have been used are incomplete, though for quite different reasons. The narrowness of the foregone earnings mea-sure is widely acknowledged. As set forth in Smith (1974), Thaler and Rosen (1976), and Viscusi (1979), the compensating earnings measure, with its emphasis upon the earnings premia workers require to be willing to be exposed to job hazards they perceive, certainly has broader analytical appeal. However, as empirically implemented, these studies too are incomplete: they deal with worker and time aggregates allowing only crude measures of differences in reward structures, mixes of complementary inputs, work-day lengths, risk aversions, worker effort, and other dissimilar factors across individuals, firms, and industries. In this paper, the productivity changes and consequent earnings adjustments that occur under differing work conditions for 17 individual citrus pickers in southern California are assessed. Interest is centered upon the acute effects of two environmental factors, ambient ozone (03) and ambient temperature, upon the daily work performances of these individuals. Since each individual is separately analyzed, the host of plausible confounding influences (e.g., experience, biological endowments, health histories, etc.) to which one must devote attention when dealing with the fictional "representative" individual are relevant here only insofar as they change within the short time periods being considered.